2016
DOI: 10.1177/0021934716653350
|View full text |Cite
|
Sign up to set email alerts
|

African American Personal Presentation

Abstract: A great amount of literature is dedicated to racial identity and self-perception, but very little addresses how hair may play a critical role in how African American women view themselves and others. African American women choose to wear their hair in a variety of styles, including weaves, wigs, dreads, chemically processed, or non-chemically processed (often referred to as "natural hair"). Researchers conducted a study that explored 282 African American females from urban and rural communities, varying in age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…S. Thompson & Keith, 2001). Studies conducted over decades and across multiple fields of study have demonstrated that colorism has measurable consequences for Black women in the United States (Choma & Prusaczyk, 2018;Drake & Cayton, 1945;Fischer & Shaw, 1999;Golden, 2004;Haizlip, 1994;Parham, 1989;Thomas, Hacker, & Hoxha, 2011;Townsend, Thomas, Neilands, & Jackson, 2010).…”
Section: Black Women and Colorism In The United Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…S. Thompson & Keith, 2001). Studies conducted over decades and across multiple fields of study have demonstrated that colorism has measurable consequences for Black women in the United States (Choma & Prusaczyk, 2018;Drake & Cayton, 1945;Fischer & Shaw, 1999;Golden, 2004;Haizlip, 1994;Parham, 1989;Thomas, Hacker, & Hoxha, 2011;Townsend, Thomas, Neilands, & Jackson, 2010).…”
Section: Black Women and Colorism In The United Statesmentioning
confidence: 99%
“…Adams et al, 2016;Mathews & Johnson, 2015;Sweet, McDade, Kiefe, & Liu, 2007). Studies also have shown that women with lighter skin fare better in the mate selection market, securing higher status spouses than their counterparts with darker skin (Drake & Cayton, 1945;Hughes & Hertel, 1990;Keith & Herring, 1991). Natural hair has largely been considered to be unprofessional, unattractive, and unfeminine, and is associated with various negative socioprofessional outcomes (e.g., lower incomes, harsher workplace conditions; B.…”
Section: Black Women and Colorism In The United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hair styling plays a significant role in human society by serving as a form of nonverbal social expression, political stance, and sexual attractiveness. 6,7 The development hair cosmeceuticals by the personal care industry is continuously changing in response to current cultural aesthetic trends. 8,9 Hair morphology can be distinguished by overall fiber shape or curl pattern.…”
Section: Introductionmentioning
confidence: 99%
“…6,8,9 Kinky hair can be further sub-classified into two different morphologies: corkscrew shape or zig-zigged, Z-angle shape. 7 Kinky hair is sometimes referred to as coily hair and people with this hair type often possess a mixture of these hair morphologies on their scalp.…”
Section: Introductionmentioning
confidence: 99%